Prediction, perception, and psychosis: Application of associative learning theories to schizophrenia research - Suzuki, Riria; Kosaki, Yutaka (Behavioral neuroscience, 2024)
In recent years, there have been significant advances in our understanding of the positive symptoms of schizophrenia, such as hallucinations and delusions. This progress has been significantly aided by the use of associative learning-based approaches in human subjects and preclinical animal models. Here, we first review experimental research focusing on the abnormal processing of absent stimuli using three different conditioning phenomena: conditioned hallucinations, mediated conditioning, and trace conditioning. We then review studies investigating the ability to reduce focal processing of physically present but informationally redundant stimuli using habituation, latent inhibition, and blocking. The results of these different lines of research are then summarized within the framework of Wagner's (1981) standard operating procedures model, an associative learning model with explicit reference to the internal representations of both present and absent stimuli. Within this framework, the central deficit associated with positive symptoms can be described as a failure to suppress the focal processing of both absent stimuli and present but irrelevant stimuli. This can explain the wide range of results obtained in different experimental settings. Finally, we briefly discuss the role of the hippocampus and its interaction with dopaminergic transmission in the emergence of such abnormal stimulus representations and learning. Overall, we hope that the theoretical framework and empirical findings offered by the associative learning approach will continue to facilitate and integrate analyses of schizophrenia conducted at the psychological and behavioral levels on the one hand, and at the neural and molecular levels on the other, by serving as a useful interface between them. (PsycInfo Database Record (c) 2024 APA, all rights reserved).